PENGARUH EXPERIENTIAL VALUE DAN PLACE FOOD IMAGE YOGYAKARTA TERHADAP BEHAVIORAL INTENTIONS WISATAWAN DOMESTIK - Nita Lintang Sekarrini; Siti Rahayu (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2018)
Tourism is principal sector in Yogyakarta, not only known for its culture but also its delicacy and diversity of the food. This study aim to determine the effect of the experiential value and place food image yogyakarta to behavioral intention of domestic tourists.